Revisiting Divisions of Labour : The impacts and legacies of a modern sociological classic - Pahl, R. E. (Raymond Edward), 1935-; Ellis, Jaimie; Crow, Graham (Book collections on Project MUSE., 2018)
Revisiting Divisions of labour is a reflection on the making of a modern sociological classic text and its enduring influence on the discipline and beyond. Ray Pahl's 1984 book is distinctive in the sustained impact it has had on how sociologists think about, research and report on the changing nature of work and domestic life. In this timely revisiting of a landmark project, excerpts from the original are interspersed with contributions from leading researchers reflecting on the book and its effects in the ensuing three decades. The book will be of interest to researchers, students and lecturers in sociology and related disciplines.